The usefulness of ultrasound in the diagnosis of patients after chest trauma – two case reports - Popiel, Agnieszka; Siwiera, Wojciech; Białas, Adam Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
The effectiveness of ultrasound in diagnosing fractures of the ribs and sternum has been confirmed in the literature. The aim of our study was to present two case reports of patients with chest trauma history in whom ultrasound examination proved useful in the diagnostic process. The role of thoracic ultrasound in the diagnosis of ribs and sternal fractures is discussed as well. The authors conclude the following: 1) the examination was easy to perform and assess, and provided clinically useful conclusions; 2) due to the mobility of the ultrasound machine, the examination may be carried out outside of radiology departments, e.g. by the patient’s bedside – in departments of surgery; 3) ultrasound should be the examination of choice after chest trauma and can be performed successfully by non-radiologist physicians.